(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2026)
This article examines the formation and development stages of English literature. It analyzes literary processes from the Middle Ages to the modern period, including major trends and prominent writers. The article also highlights the influence of literature on society and human thinking.